Callitriche stagnalis Scopoli 1772 - Lansdown, Richard V.; Hassemer, Gustavo (Zenodo, 2021)
20. Callitriche stagnalis Scopoli (1772: 251) Type: — UNITED KINGDOM. CARDIGANSHIRE: Aberleri Fields, Borth, Cards 22/61209160, 20 July 1998, A.O. Chater s.n. (neotype [designated by Lansdown 2006b: 108] NMW!). Description: —Stem and leaf scales present. Leaf bases connate. Lingulate leaves very rare, usually lacking, expanded submerged or floating leaves variable, from broadly parallel-sided, through obovate spathulate to almost circular, 2.7–21.4(–21.7) × 1.4–8.3 mm, petiole 0.7–6.5(–7.5) mm, venation simple or complex with numerous loops and anastomosing veins, the apical leaves forming a floating rosette, leaves of terrestrial plants narrowly elliptic 2.6–4.4 × 1.6–3.3 mm, petiole 0.8–2.1 mm. Flowers usually solitary. Bracts falcate, persistent 0.6–2.6(–2.9) mm. Styles erect, becoming recurved in fruit, ≤ 6 mm. Filaments erect, becoming recurved and continuing to grow after dehiscence; ≤ 16.2 mm; anthers reniform, 0.3–0.9 mm diameter; pollen yellow. Fruit not strumose, subsessile or occasionally very shortly-pedicellate, ± as wide as high, greyish when mature, 1.1–1.8 × 1.1–2.0 mm, winged throughout. Illustrations: —figures on pages 81 and 83 in Lansdown (2008); Figure 5 (i). Distribution: — Callitriche stagnalis is native to Europe, from the Azores to Iceland and east to the western side of the Ural Mountains in Russia (Lansdown 2006a). It also occurs as an alien (naturalised) in North America (Philbrick et al. 1998), Australia (Orchard 1980), New Caledonia and New Zealand (Mason 1959). Two specimens are known from South America, one from Biobío Province in Chile and one from the Falkland Islands. Notes: — Callitriche stagnalis was reported in error from Brazil, but recognised as occurring as a non-native in Chile and the Falkland Islands (Lansdown & Hassemer 2018). It can be distinguished from all other Callitriche species in the region bY the large fruit (> 1 mm diameter), long stYle (≤ 6 mm long) and long filament (≤ 16 mm long). Conservation status: — Callitriche stagnalis is classed as Least Concern (LC) because it is widespread and abundant through much of its native range. Additional material studied: —[only South American specimens listed] CHILE: BIOBÍO: Submersed in shallow pools in grazed salt marsh, just beYond the PetroX refinerY, Estero Lenga 2.5 km west of Abda. Gran Bretaňa on Avda. Los Golondrinas, Concepción Province, 22 October 1990, T.G. Lammers et al. 7503 (F). UNITED KINGDOM. FALKLAND ISLANDS: Ditches/drainage, Stanley, East Falkland, seeds collected for MSB (MSB FI 51), growing with Juncus scheuzeroides , Agrostis sp., Holcus lanatus , Anthoxanthum odoratum and Juncus bufonius , 2 March 2009, R. Lewis 520786 (K barcode K000299348). : Published as part of Lansdown, Richard V. & Hassemer, Gustavo, 2021, The genus Callitriche (Plantaginaceae: Callitricheae) in South America, pp. 85-118 in Phytotaxa 501 (1) on pages 109-110, DOI: 10.11646/phytotaxa.501.1.3, http://zenodo.org/record/5424744 : {"references": ["Scopoli, J. A. (1772) Flora carniolica, 2 nd ed. J. P. Krauss, Vienna, 496 pp.", "Lansdown, R. V. (2006 b) Notes on the water-starworts (Callitriche) recorded in Europe. Watsonia 26: 105 - 120.", "Lansdown, R. V. (2008) Water starworts of Europe. BSBI Handbook No. 11. Botanical Society of the British Isles, London.", "Lansdown, R. V. (2006 a) The genus Callitriche (Callitrichaceae) in Asia. Novon 16: 354 - 361. https: // doi. org / 10.3417 / 1055 - 3177 (2006) 16 [354: TGCCIA] 2.0. CO; 2", "Philbrick, C. T., Aakjar Jr., R. A. & Stuckey, R. L. (1998) Invasion and spread of Callitriche stagnalis (Callitrichaceae) in North America. Rhodora 100: 25 - 38.", "Orchard, A. E. (1980) Callitriche (Callitrichaceae) in South Australia. Journal of the Adelaide Botanic Garden 2: 191 - 194.", "Mason, R. (1959) Callitriche in New Zealand and Australia. Australian Journal of Botany 7: 295 - 327. https: // doi. org / 10.1071 / BT 9590295"]}